Pharmacokinetic and pharmacodynamic modelling of intravenous, intramuscular and subcutaneous buprenorphine in conscious cats - Steagall, Paulo V.M. [UNESP]; Pelligand, Ludovic; Giordano, Tatiana [UNESP]; Auberger, Christophe; Sear, John W.; Luna, Stélio Pacca Loureiro [UNESP]; Taylor, Polly M. (Elsevier, 2013)
Objective To describe simultaneous pharmacokinetics (PK) and thermal antinociception after intravenous (IV), intramuscular (IM) and subcutaneous (SC) buprenorphine in cats. Study design Randomized, prospective, blinded, three period crossover experiment. Animals Six healthy adult cats weighing 4.1±0.5kg. Methods Buprenorphine (0.02mgkg-1) was administered IV, IM or SC. Thermal threshold (TT) testing and blood collection were conducted simultaneously at baseline and at predetermined time points up to 24hours after administration. Buprenorphine plasma concentrations were determined by liquid chromatography tandem mass spectrometry. TT was analyzed using anova (p<0.05). A pharmacokinetic-pharmacodynamic (PK-PD) model of the IV data was described using a model combining biophase equilibration and receptor association-dissociation kinetics. Results TT increased above baseline from 15 to 480minutes and at 30 and 60minutes after IV and IM administration, respectively (p<0.05). Maximum increase in TT (mean±SD) was 9.3±4.9°C at 60minutes (IV), 4.6±2.8°C at 45minutes (IM) and 1.9±1.9°C at 60minutes (SC). TT was significantly higher at 15, 60, 120 and 180minutes, and at 15, 30, 45, 60 and 120minutes after IV administration compared to IM and SC, respectively. IV and IM buprenorphine concentration-time data decreased curvilinearly. SC PK could not be modeled due to erratic absorption and disposition. IV buprenorphine disposition was similar to published data. The PK-PD model showed an onset delay mainly attributable to slow biophase equilibration (t1/2ke0=47.4minutes) and receptor binding (kon=0.011mL ng-1minute-1). Persistence of thermal antinociception was due to slow receptor dissociation (t1/2koff=18.2minutes). Conclusions and clinical relevance IV and IM data followed classical disposition and elimination in most cats. Plasma concentrations after IV administration were associated with antinociceptive effect in a PK-PD model including negative hysteresis. At the doses administered, the IV route should be preferred over the IM and SC routes when buprenorphine is administered to cats. © 2012 Association of Veterinary Anaesthetists and the American College of Veterinary Anesthesiologists.
Keywords: Analgesia; Buprenorphine; Cat; Pharmacokinetics; Routes of administration; Thermal nociceptive threshold; buprenorphine; narcotic analgesic agent; animal; animal disease; blood; cat; controlled clinical trial; controlled study; crossover procedure; female; intramuscular drug administration; intravenous drug administration; male; randomized controlled trial; subcutaneous drug administration; Analgesics, Opioid; Animals; Cats; Cross-Over Studies; Female; Injections, Intramuscular; Injections, Intravenous; Injections, Subcutaneous; Male; Animalia